Dynamics of Myopia Progression in Ghana—Evidence From Clinical Practice: A Retrospective Cohort Study - Samuel Kyei; Godwin Avornyo; Randy Asiamah; Samuel B. Boadi‐Kusi; Michael Agyemang Kwarteng (Health Science Reports)
ABSTRACT Background and Aim To investigate the pattern of progression of myopia among a Ghanaian clinical cohort. Methods A retrospective cohort analysis of a clinical data set of all healthy myopic participants attending a tertiary eye care center was performed. Participants' biennial refraction examinations were tracked for refractive changes 4 years after the date of the first visit. This covered the period from January 2015 to December 2019. Myopia progression was defined as a difference in spherical equivalent between consecutive biennial visits equal to, or greater than −0.50 D of myopia. Results The medical records of 169 myopic participants were reviewed, with the majority (53.8%) being female. Most of the participants (51.4%) were younger than 36 years, and at the end of the study period, 96 participants (56.8%), who made up the majority, showed progression of myopia Univariate regression revealed that the 36–59‐year‐old age range is associated with a 60% [cOR = 0.40, 95% CI: –0.17, 0.97; p = 0.04] reduced likelihood compared to those belonging to the 0–17‐year‐old age group, and the Mole‐Dagbon ethnicity is associated with an almost fourfold [cOR = 3.80; 95% CI: –1.40, 10.316; p = 0.01] increased likelihood of experiencing myopia progression compared to those of Ga‐Adangbe ethnicity. Multivariate regression revealed that the Mole‐Dagbon ethnicity is associated with an increased likelihood of experiencing myopia progression 4 years after their initial visit [aOR = 3.49; 95% CI: –1.27, 9.63; p = 0.02] compared to those of Ga‐Adangbe ethnicity. Conclusion Our study provides important insights into myopia progression in Ghana, with findings that are consistent with global trends. The association of myopia progression with age, place of residence, degree of myopia, and ethnicity highlights the need for tailored interventions to manage this growing public health concern in African populations.